A Method of Friction Disturbance Compensation Based on Velocity Feedback - Jianwen Zhao; Shengrong Fan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The friction disturbance influences servo system in follow-up performance directly, active compensation for the friction disturbance can improve the servo performance. The current compensation algorithms have some disadvantages, such as the complication of algorithms and the high requirement on hardware. In this paper, we propose a new method based on velocity observer. By this method, analytic solution of compensation voltage can be obtained aim to friction disturbance. The method is validated by comparing the results between simulation and experiment. This method has advantages of low requirement on hardware and simple algorithm. It is easy to be applied in practice and provides reference to other servo system for compensation of disturbance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2810